Penerapan Sistem Akuntansi Penerimaan dan Pengeluaran Kas pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Sumatera Utara - Aditya Fadillah; Nurbaiti Nurbaiti (Universitas Muhammadiyah Enrekang, 2022)
The purpose of conducting this research was to find out how the application of the accounting system to cash receipts and disbursements at the Regional Financial and Asset Management Agency of North Sumatra Province. Accountability (accountability) of government is manifested in LAKIP or Performance Accountability Reports of Government Agencies which are reports that show the form of government financial performance accountability to the public for one fiscal year. Every rupiah of public money that has been given to finance development and the running of the government is accounted for by the government. The research method of this journal is using qualitative research methods. The result of this study is that the implementation of regional asset management has been running in accordance with the regulations that have been made. It's just that there are some lack of data and the number of terms and conditions and status of real estate ownership and databases that are appropriate for preparing regional government balance sheets.